Redefining Orientalism Through “Squid Game”: Sentiment Analysis And Word Cloud R Studio - Moh Rifaldi Akbar (Universitas Lambung Mangkurat, 2024)
This article aims to redefine Edward Said's definition of orientalism in the era of contemporary communication and information technology through the comments column for the film Squid Game on the IMDB (internet movie database) website. This paper argues that the Orientalist attitude of a dominant English-speaking country such as the United States emerged as a consequence of its white superior hegemony. In the midst of this orientalist attitude, today's communication and information technology has become a discursive channel for the world community to conduct ongoing discussions on films by Asians. By using the text in the comment column for the film Squid Game on IMDB.com as a case example, this article provides a discussion regarding the need to rethink the conceptual definition of orientalism today. This paper uses a digital research methodology with analysis tools using R Studio with two types of analysis, namely word cloud and sentiment analysis. By utilizing the programming language functions available in R Studio, this paper mines text from the IMDB.com comments column for the film Squid Game. This article contains results obtained from digital research methods, namely the Squid Game comments column focuses on characters, plot, acting and story. Meanwhile, sentiment analysis shows the dominance of positive sentiment and some negative sentiment. Therefore, this article argues that the battle between negative and positive sentiments in the Squid Game comments column is a means of resetting the negative stigma towards Asian films and eroding the orientalist attitudes that the West oppresses towards